Introduction to Magnetic Resonance Imaging for Neurologists. Issue 5 (October 2016) - Radue, Ernst-Wilhelm; Weigel, Matthias; Wiest, Roland; Urbach, Horst
Abstract : ABSTRACT: Purpose of Review: In neuroradiology, highly sophisticated methods such as MRI are implemented to investigate different entities of the central nervous system and to acquire miscellaneous images where tissues display varying degrees of characteristic signal intensity or brightness. Compared to x-ray, CT, and ultrasound, MRI produces clearer images of tissues, body fluids, and fat. The basics of MRI may be unknown to neurologists; this article introduces MRI physics, techniques, and interpretation guidelines. Recent Findings: This article discusses the basics of MRI to provide clinicians with the scientific underpinning of MRI technology and to help them better understand image features and improve their diagnosis and differential diagnosis by combining MRI characteristics with their knowledge of pathology and neurology. Summary: This article will help neurologists deepen their knowledge and understanding of MRI by introducing the basics of MRI physics, technology, image acquisition, protocols, and image interpretation.